2022
DOI: 10.1001/jamaneurol.2022.0888
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Hippocampal Epileptiform Activity on Scalp Electroencephalogram

Abstract: IMPORTANCEThe hippocampus is a highly epileptogenic brain region, yet over 90% of hippocampal epileptiform activity (HEA) cannot be identified on scalp electroencephalogram (EEG) by human experts. Currently, detection of HEA requires intracranial electrodes, which limits our understanding of the role of HEA in brain diseases.OBJECTIVE To develop and validate a machine learning algorithm that accurately detects HEA from a standard scalp EEG, without the need for intracranial electrodes. DESIGN, SETTING, AND PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…This study also suggests that HFOs could be a new biomarker in AD. The ability to record HFOs and epileptiform activity from different brain areas, and do so noninvasively, [50][51][52] strengthens that view. Additional benefits include the ability to conduct EEG recordings repeatedly over time to characterize disease progression.…”
Section: Author Contributionsmentioning
confidence: 99%
“…This study also suggests that HFOs could be a new biomarker in AD. The ability to record HFOs and epileptiform activity from different brain areas, and do so noninvasively, [50][51][52] strengthens that view. Additional benefits include the ability to conduct EEG recordings repeatedly over time to characterize disease progression.…”
Section: Author Contributionsmentioning
confidence: 99%
“…This study also suggests that HFOs could be a new biomarker in AD. The ability to record HFOs and epileptiform activity from different brain areas, and do so non-invasively, [49][50][51] strengthens that view. Additional benefits include the ability to conduct EEG recordings repeatedly over time to characterize disease progression.…”
Section: Concluding Remarks and Considerationsmentioning
confidence: 84%
“…A recent study showed that with the aid of artificial intelligence it is even possible to detect hippocampal epileptiform activity in the scalp EEG 88 . Simultaneous recordings of OPM- and EEG-data would enable a direct comparison between the two modalities regarding their ability to identify hippocampal IEDs.…”
Section: Discussionmentioning
confidence: 99%